Morphogenesis and biomass production of ’BRS Tamani’ guinea grass under increasing nitrogen doses - Vasconcelos, Elayne Cristina Gadelha; Cândido, Magno José Duarte; Pompeu, Roberto Cláudio Fernandes Franco; Cavalcante, Ana Clara Rodrigues; Lopes, Marcos Neves (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the morphogenic and structural characteristics of Megathyrsus maximus 'BRS Tamani', subjected to increasing nitrogen doses, as well as the components of its biomass. The experiment was carried out in a randomized complete block design with four treatments (0, 300, 600, and 1,200 kg ha-1 N per year) and three replicates, in 12 experimental units of 12.5 m² each. The evaluations were performed in the rest period of the pasture, after defoliation to a residual leaf area index of 1.0, until the pasture reached the number 3.0 of new leaves produced per tiller. Leaf and stem elongation rates increased with the increment in N doses up to 1,200 kg ha-1 N per year. There was a decreasing linear response for phyllochron and leaf life span. Increases of 704% were observed for the harvestable green leaf biomass, at the dose equivalent to 1,200 kg ha-1 N per year. The biomasses of dead forage and harvestable stem were not affected by the N doses. Nitrogen fertilization shows a positive effect on the morphogenic, structural, and productive characteristics of 'BRS Tamani' guinea grass up to the dose equivalent to 1,200 kg ha-1 N per year.